Extracellular Vesicle Heterogeneity: Subpopulations, Isolation Techniques, and Diverse Functions in Cancer Progression - Willms, Eduard; Cabañas, Carlos; Mäger, Imre; Wood, Matthew J. A.; Vader, Pieter (Frontiers in Immunology, 2018)
Cells release membrane enclosed nano-sized vesicles termed extracellular vesicles (EVs) that function as mediators of intercellular communication by transferring biological information between cells. Tumor-derived EVs have emerged as important mediators in cancer development and progression, mainly through transfer of their bioactive content which can include oncoproteins, oncogenes, chemokine receptors as well as soluble factors, transcripts of proteins and miRNAs involved in angiogenesis or inflammation. This transfer has been shown to influence the metastatic behavior of primary tumors. Moreover, tumor-derived EVs have been shown to influence distant cellular niches, establishing favorable microenvironments that support growth of disseminated cancer cells upon their arrival at these pre-metastatic niches. It is generally accepted that cells release a number of major extracellular vesicle (EV) populations with distinct biophysical properties and biological functions. Exosomes (EXOs), microvesicles (MVs) and apoptotic bodies (APOs) are EV populations most widely studied and characterized. They are discriminated based primarily on their intracellular origin. However, increasing evidence suggests that even within these EV populations various subpopulations may exist. This heterogeneity introduces an extra level of complexity in the study of EV biology and function. For example, EV subpopulations could have unique roles in the intricate biological processes underlying cancer biology. Here, we discuss current knowledge regarding the role of subpopulations of EVs in cancer development and progression and highlight the relevance of EV heterogeneity. The position of tetraspanins and integrins therein will be highlighted. Since addressing EV heterogeneity has become essential for the EV field, current and novel techniques for isolating EV subpopulations will also be discussed. Further dissection of EV heterogeneity will advance our understanding of the critical roles of EVs in health and disease.